Developing Vaccine Literacy for Urban Health Science Students, the Future Health Workforce - Naydu Carmona; Monica Trujillo (Journal of Microbiology & Biology Education, 2023)
ABSTRACT The 2019 coronavirus disease pandemic underlined a shift in attitudes against vaccines and a rise in hesitancy among some members of the population, despite the overwhelming evidence that vaccinations are one of the most successful and safe health interventions. Research has shown that vaccine hesitancy is complex and can result from an intersectionality of multiple factors. Research has also shown that to tackle vaccine hesitancy in the community, health care workers play a pivotal role, as they are trusted sources who can provide reliable information and can address vaccination concerns for the public. Unfortunately, health care workers are also susceptible to vaccine hesitancy. Thus, to curb these negative attitudes and doubts against vaccinations, we propose to improve vaccine competency among health science students, who are the future health workforce. Here, we propose a comprehensive pedagogical approach that aims to improve the vaccine literacy in this student population in two urban community colleges. The approach includes the use of high-impact pedagogical interventions to achieve three main objectives: (i) to teach students the nature and process of science to have them become “competent outsiders”; (ii) to enhance students’ knowledge of the complex science behind emerging infectious diseases and vaccine action, adopting a learner-centered and concept-focused instructional design, and (iii) to address the social, cultural, and historical aspects of vaccine development and the historical and present inequities that characterize this health intervention.